Clinical and pathological characteristics of peripheral T‐cell lymphomas in a Spanish population: a retrospective study. (19th May 2020) - Rodriguez‐Pinilla, Socorro Maria; Domingo‐Domenech, Eva; Climent, Fina; Sanchez, Joaquin; Perez Seoane, Carlos; Lopez Jimenez, Javier; Garcia‐Cosio, Monica; Caballero, Dolores; Blanco Muñez, Oscar Javier; Carpio, Cecilia; Castellvi, Josep; Martinez Pozo, Antonio; et al.
Abstract: We investigated the clinicopathological features and prognostic factors of patients with peripheral T‐cell lymphoma (PTCL) in 13 sites across Spain. Relevant clinical antecedents, CD30 expression and staining pattern, prognostic indices using the International Prognostic Index and the Intergruppo Italiano Linfomi system, treatments, and clinical outcomes were examined. A sizeable proportion of 175 patients had a history of immune‐related disorders (autoimmune 16%, viral infections 17%, chemo/radiotherapy‐treated carcinomas 19%). The median progression‐free survival (PFS) and overall survival (OS) were 7·9 and 15·8 months, respectively. Prognostic indices influenced PFS and OS, with a higher number of adverse factors resulting in shorter survival ( P  < 0·001). Complete response (CR) to treatment was associated with better PFS (62·6 vs. 4 months; P  < 0·001) and longer OS (67·0 vs. 7·3 months; P  < 0·001) compared to no CR. CD30 was expressed across all subtypes; >15% of cells were positive in anaplastic lymphoma kinase‐positive and ‐negative anaplastic large‐cell lymphoma and extranodal natural killer PTCL groups. We observed PTCL distribution across subtypes based on haematopathological re‐evaluation. Poor prognosis, effect of specific prognostic indices, relevance of histopathological sub‐classification, and response level to first‐line treatment on outcomes were confirmed. Immune disorders amongst patients require further examination involving genetic studies and identification of associated immunosuppressive factors.